Жуть вампирская: [рассказы, сказочная повесть] / Алексей Лисаченко ; художник Д. Лапшина - Лисаченко Алексей Владимирович (Страшилки, 2020)
Экземпляры: ДО ст.аб. (2023) / Инвентарный номер: 59083 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 63 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44